EVOLUTION OF THE AGRICULTURAL LABOUR MARKET IN THE EUROPEAN UNION BETWEEN 2011-2020 - Cristina Vasilica ICOCIU; Ana-Maria IFRIM; Cătălin Ionuț SILVESTRU; Marius-Mihai MICU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the current context, in which the pandemic crisis is wreaking havoc in all socio-economic fields, causing both loss of life and immeasurable economic losses, fundamental research conducted to identify directions for rapid and sustainable socio-economic recovery is of great importance. Over time, the agricultural sector has played a particularly important role in accelerating the expansion and economic development of the least developed countries and their integration into world trade. The basic hypothesis is that, over time, agriculture has been the premise for the economic development of the world's states, the agricultural transition being quite well correlated with general growth processes. By improving their competitiveness and strengthening their agricultural production capacities, the countries of the world can recover from any crisis, especially after a health crisis. The work aims to present the possible impact that agriculture can have on economic development by applying known principles and foundations. Making investments in agriculture, increasing the level of employability leads to the development of this branch of the economy and implicitly of the other branches of industry that are connected with agriculture, such as the food industry. Using a mathematical algorithm for studying the impact of the evolution of the agricultural labour (salaried) in the context in which it is desired that agriculture be a sustainable branch from the point of view of employability at the level of the European Union. The results of this study can then be materialized in strategic directions of development of every country, in the hope of moving to another level of development. In the context in which agriculture is the basis for the horizontal development of other industries (such as the food industry) it is necessary to carry out an investment program and research programs in the agricultural field. Applying Lewis's model of development, governments must strive to increase agricultural productivity while stimulating capital accumulation and in the other sectors of the economy.